Microbiota-derived metabolites in tumorigenesis: mechanistic insights and therapeutic implications - Yang, Si-Fu; Chen, Xiao-Chen; Pan, Yao-Jie (Frontiers in Pharmacology, 2025)
Intestinal microbiota is a complex ecosystem of microorganisms that perform diverse metabolic activities to maintain gastrointestinal homeostasis. These microorganisms provide energy and nutrients for growth and reproduction while producing numerous metabolites including lipopolysaccharides (LPS), Bacteroides fragilis toxin (BFT), bile acids (BAs), polyamines (PAs), and short-chain fatty acids (SCFAs). These metabolites are linked to inflammation and various metabolic diseases, such as obesity, type-2 diabetes, non-alcoholic fatty liver disease, cardiometabolic disease, and malnutrition. In addition, they may contribute to tumorigenesis. Evidence suggests that these microbes can increase the susceptibility to certain cancers and affect treatment responses. In this review, we discuss the current knowledge on how the gut microbiome and its metabolites influence tumorigenesis, highlighting the potential molecular mechanisms and prospects for basic and translational research in this emerging field.